[Image 09] - Smith, Captain Sir William [?ob. 1732] (My University, 1804)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of the Inn and Malin Well in the barony of Inishowen Co: of Donegal drawn as looking the way of the signal station created & built by Sir Wm Smith in 1804.
Keywords: Malin Well; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810